Leadership Psychology: How Effective Leaders Manage Emotions in Organizations - Mohammad Bilutfikal Khofi (Yayasan Adra Karima Hubbi, 2024)
This research explores how effective leaders manage their emotions in organizations, focusing on practical strategies that can be used in real-life situations. This research will use a literature review approach. The literature used in this research will be taken from various credible academic sources, including scholarly journals, books, and articles from Google Scholar. Keywords such as